Calcium biofortification of Rocha pears, tissues accumulation and physicochemical implications in fresh and heat-treated fruits - Pessoa, Cláudia Campos (2022)
Low dietary intake of Ca in humans has been epidemiologically linked to various diseases, which can have serious health consequences over time. Accordingly, the development of an agronomic itinerary for Ca biofortification of Rocha pears and the assessment of physicochemical deviations prompted this study. Two orchards with contrasting soil and water characteristics were selected, characterized through orthophotomaping and, during fruits development, leaves were sprayed twice with Ca(NO3)2 (0.1, 0.3 and 0.6 kg ha - 1) or CaCl2 (0.4, 0.8 and 1.6 kg ha - 1), followed by pulverization only with CaCl2 (first once with 4 kg ha - 1 and then four times with 8 kg ha - 1). During fruits development net photosynthesis, stomatal conductance, transpiration rates, instantaneous and water use efficiency, only showed minor deviations, which indicated that the threshold of toxicity was not surpassed. Calcium contents varied during fruits development and at harvesting the average biofortification index varied between 47 %–63 % and 24 %–59 % in each of the orchards. Besides, the equatorial region of the fruits showed for all treatments (substantially in Ca treated samples) higher Ca contents in the epidermal and in the central regions. Fresh and heat-treated fruits (in a thermomix at 90 ◦C, during 10 min) biofortified with Ca only revealed minor differences and the sensory acceptability did not vary markedly. It is concluded that, although prevailing a heterogeneous distribution of Ca in fruit tissues, high indexes of biofortification in Rocha pears can be prompt in the orchards, without substantial physicochemical changes. Accordingly, agronomic biofortification with Ca can be used as a strategy for benefiting consumer’s health